Green Nephrology: Promoting Sustainability in Healthcare. - Kumar, Mukesh; Mal, Pooran (Pakistan Journal of Kidney Diseases, 2025)
Climate change is a serious threat to human health, affecting not just the natural environment but also all aspects of human and ecological systems. As a result, it exacerbates existing issues, threatening to undermine and even reverse years of progress in health and well-being. Green Nephrology stresses sustainable approaches to reduce environmental effect while providing great care to patients. By incorporating sustainability into everyday operations, we can lower nephrology’s environmental footprint while still providing life-saving therapies.